Особливості оформлення кладовищ декоративними насадженнями та квітковими композиціями - Kushnir, О.А. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
There are classifications of decorative plants of burial places: the basic conditions which influence on horticulture style choice and assortment of plants, most frequently used on cemeteries in the article.